Sobre a crítica da moral e a transvaloração dos valores segundo Friedrich Nietzsche - Alves, Cícero Everardo de Oliveira (2015)
The general purpose of this research is to expose the thought of Friedrich Nietzsche about the notion of value in order to present his critique to the foundations of traditional morality, and consequently understand what are the determinations that constitute the project that this philosopher designated as revaluation of all values. In this trajectory, we question according to the Nietzschean thought the way that the moral values become accepted, as the ones have historically been instituted and what underlies as a foundation in order to clarify that the criticism of moral values is directlyrelated to the notion of value. From this, the research undertakes an analysis of the elements of his critique to the modern culture, seeking an understanding of the factors that possibly entail a loss of existence meaning. We are going to discuss the notions that Nietzsche had used in his efforts to solve the aporias originated both from pessimism problematic as asceticism, both of them rooted in the spirit of the modern man. In this research, you will the way this philosopher reflects on the overcoming of assumptions that express ideals of perhaps decadent nature and which encourage also the animal man belittlement. Indeed, a debate about the revaluation project of all values there would not be to dodge from these issues, rather the understanding of such minutiae are taken as greater scope, since through the articulation of these elements we shall know how the project mentioned above not only makes up Nietzsche's critique to the morality, but ended by being characterized as truly decisive moment of his philosophical production.